2015
DOI: 10.1080/15427528.2014.995328
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Application of Pyroligneous Acid in the UK Agricultural Industry

Abstract: This paper highlights the potential benefits of smoke recovery from the production of biochar in crop management through it application as an antimicrobial agent against plant disease and as a pesticide. The study reports on the findings of zone inhibition assays on selected plant pathogens ( Agrobacterium tumefacien and Xanthomonas campestris), growth studies on selected plants ( Raphanus sativus and Vicia faba), and toxicity studies performed on arthropods ( Myzus persicae and Tetranychus urticae). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Wood distillate can be applied to promote plant development and increase crop productivity and quality [ 21 ]. Its chemical composition is quite complex, but is mainly characterized by high contents of acetic acid, phenols and esters, which stimulate antioxidant [ 22 , 23 , 24 ] and antimicrobial properties [ 25 , 26 ] and enhance plant growth [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wood distillate can be applied to promote plant development and increase crop productivity and quality [ 21 ]. Its chemical composition is quite complex, but is mainly characterized by high contents of acetic acid, phenols and esters, which stimulate antioxidant [ 22 , 23 , 24 ] and antimicrobial properties [ 25 , 26 ] and enhance plant growth [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mmojieje et al prepared WV from mixed wood biomass and investigated its pesticidal effects on the red spider mite and green peach aphid, which showed that WV exhibited more than 90% mortality for both pests. 12 Lashari et al found that WV has a beneficial effect on leaching soluble salts, decreasing the soil pH and resulting in the improvement of crop productivity in saline soils. 13 Many studies report the regulatory effects of WVs on seed germination and plant growth in sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are essential for plant growth and reproduction and as protective agents, being secreted as a defense mechanism (Vicente and Boscaiu, 2018). Other studies have confirmed the efficiency of pyroligneous acid in inhibiting bacteria (Mmjieje and Hornung, 2015;Zhang et al, 2019) and fungus as Rhizoctonia solani (Hossain et al, 2015), Colletotrichum gloeosporioides (Ribeiro et al, 2016) and Botryodiplodia theobromae (Theapparat et al, 2015).…”
Section: Methodsmentioning
confidence: 92%
“…Results from other studies confirm the efficiency of lime sulfur as a fungicide in the control of Stemphylium solani in vitro (Domingues et al, 2017) and angular leaf spot in common bean crop (Carvalho et al, 2010). According to Ming et al (2012), the reduction in the rate of fungal leaf diseases in sweet passion fruit crop can be explained by the fact that lime sulfur contains sulfur, which acts as a phytoprotective agent, in addition to the fungistatic action. The application of lime sulfur in this study led to a reduction in severity, compared to the control, without, however, highlighting in disease control, which also occurred in the study by Mazaro et al 2013, in which there was no significant reduction in the area below the disease progress curve with the application of the syrup, but there was a reduction in mycosphaerella severity in strawberry.…”
Section: Methodsmentioning
confidence: 99%